2021
DOI: 10.7759/cureus.18522
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Rhabdomyolysis in the Bilateral Shoulder Areas After Cardiac Surgery

Abstract: Rhabdomyolysis (RML) is a disease that results from the death of muscle fibers and the release of intracellular contents into the bloodstream as a result of traumatic or non-traumatic muscle injury. Postoperative RML is a rare complication that may result from improper patient positioning, extended surgery time, or unique patient risk factors. We describe a case of a 43-year-old obese male who presented with postoperative bilateral shoulder RML after undergoing cardiothoracic surgery for aortic valve disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Rhabdomyolysis following surgery is a recognized complication that might be brought on by the patient's position, an extended procedure, or certain postoperative risk factors, with numerous reports detailing its impact on the management of the common indications for which patients undergo surgery (3,4). Aneurysmal subarachnoid haemorrhage(aSAH) is a relative reason for prolonged surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Rhabdomyolysis following surgery is a recognized complication that might be brought on by the patient's position, an extended procedure, or certain postoperative risk factors, with numerous reports detailing its impact on the management of the common indications for which patients undergo surgery (3,4). Aneurysmal subarachnoid haemorrhage(aSAH) is a relative reason for prolonged surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Improper positioning during long-lasting surgery can cause a large amount of body weight to be focused on a specific region over a long period, leading to severe muscle damage. Studies published by researchers from various fields, including bariatric surgery, cardiac surgery, and neurosurgery, have demonstrated that body regions in contact with the operating table during long-lasting surgery are subjected to high pressure when the patient’s position does not change after anesthesia, substantially increasing the risk of postoperative rhabdomyolysis ( 3 - 5 ).…”
Section: Introductionmentioning
confidence: 99%